FOLLOW-UP OF ELECTROPHYSIOLOGICAL PARAMETERS OF CARDIAC ACTIVITY IN PRETERM INFANTS WITH PERINATAL DISORDERS OF THE CENTRAL NERVOUS SYSTEM - B.A. Bezkaravayny; G.A. Solovyova (Bukovynian State Medical University, 2019)
The article presents the results of prospective observation of the 160 preterm infants with perinatal disorders of CNS. Analysis of heart rate indices according prolonged ECG monitoring showed positive dynamics of heterotopic activity reducing and reliable improvement of the functional state of the conduction system of the heart in all premature infants aged 20-30 months of life after the course of timely rehabilitation therapy of perinatal disorders of CNS.